Do Islamic Financial Instruments and Inflation Affect Economic Growth in Indonesia? - Srie Shailla Meidhany; Early Ridho Kismawadi; Zulkarnaini Zulkarnaini; M. Irvanni Bahri (Journal of Finance and Islamic Banking, 2022)
This research aimed to see how sharia stocks, Sukuk, sharia mutual funds, and inflation affected economic development. This is a quantitative analysis based on secondary data from 2012 to 2019. Multiple linear regression equations, t-test, F test, and coefficient of determination are examples of data analysis methods (R2). According to the multiple linear regression equation test findings, sharia stocks, Sukuk, and sharia mutual funds have a favorable impact on Indonesian economic development, but inflation has a negative effect. The findings of the t-test show that sharia stocks and inflation have a considerable impact on Indonesian economic development, but Sukuk and sharia mutual funds have no such impact. The F test findings reveal that sharia equities, Sukuk, sharia mutual funds, and inflation have a major impact on Indonesian economic development. The coefficient of determination (R2) test findings show that sharia equities, Sukuk, sharia mutual funds, and inflation may all be used to explain economic development..